2010
DOI: 10.1377/hlthaff.2009.0400
|View full text |Cite
|
Sign up to set email alerts
|

Trends In Health Care Spending For Immigrants In The United States

Abstract: The suspected burden that undocumented immigrants may place on the U.S. health care system has been a flashpoint in health care and immigration reform debates. An examination of health care spending during 1999-2006 for adult naturalized citizens and immigrant noncitizens (which includes some undocumented immigrants) finds that the cost of providing health care to immigrants is lower than that of providing care to U.S. natives and that immigrants are not contributing disproportionately to high health care cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 12 publications
4
52
0
Order By: Relevance
“…3 The question of immigrants' use of health services has been addressed by a group of recent studies, all of which have concluded that health care use and spending are lower among immigrants than among people born in the United States. [4][5][6][7][8][9][10][11][12][13] One recent report compared differences in access to care by nativity and legal status and found that the percentage of unauthorized immigrants who lack health insurance has been growing over the past few years, and that there doi: 10 were persistent differences in uninsurance rates across immigration statuses, even after poverty levels were accounted for. 14 These findings imply that restricted access to health insurance among unauthorized immigrants potentially translates into higher out-ofpocket health spending for immigrants and higher costs to providers of uncompensated care for immigrants.…”
mentioning
confidence: 99%
“…3 The question of immigrants' use of health services has been addressed by a group of recent studies, all of which have concluded that health care use and spending are lower among immigrants than among people born in the United States. [4][5][6][7][8][9][10][11][12][13] One recent report compared differences in access to care by nativity and legal status and found that the percentage of unauthorized immigrants who lack health insurance has been growing over the past few years, and that there doi: 10 were persistent differences in uninsurance rates across immigration statuses, even after poverty levels were accounted for. 14 These findings imply that restricted access to health insurance among unauthorized immigrants potentially translates into higher out-ofpocket health spending for immigrants and higher costs to providers of uncompensated care for immigrants.…”
mentioning
confidence: 99%
“…Immigrants have been accused of overusing services, which places a burden on taxpayer-supported systems such as AHCCCS in Arizona (Ortega et al, 2007;Stimpson, Wilson, & Eschbach, 2010). However, because of the challenges of identifying and sampling the undocumented population, only limited empirical data are available in the literature.…”
Section: Impact and Implications Of Undocumentedness: Public Health Imentioning
confidence: 99%
“…A study conducted in Los Angeles (Goldman, Smith, & Sood, 2006) reported that in comparison with U.S.-born Mexicans, undocumented Mexicans had 1.6 fewer physician visits, were less likely to report difficulty obtaining necessary N u r s O u t l o o k 6 3 ( 2 0 1 5 ) 7 7 e 8 5 health care, and were less likely to have a usual source of care and to report negative experiences. In terms of the impact on health care costs, a study that used data from the 1999e2006 Medical Expenditure Panel Surveys (Stimpson et al, 2010) reported that overall, noncitizen immigrants had proportionately lower public health expenditures than U.S. natives and naturalized citizens but were more likely than U.S. natives to have uncompensated care costs for a health care visit. These findings show that immigrant authorization status and low socioeconomic status are important determinants of health care access and service use and have implications for efforts to eliminate health care disparities among this vulnerable population (Ortega et al, 2007).…”
Section: Impact and Implications Of Undocumentedness: Public Health Imentioning
confidence: 99%
“…Recent studies have attempted to dispel these beliefs, indicating that undocumented immigrant may not be contributing to the increase in healthcare costs in the U.S. and that addressing healthcare needs of this population could in fact reduce costs (Mohanty, Woolander, Himmelstein, et al, 2005;Stimpson, Wilson & Eschbach, 2010). Research findings from this study also dispelled these common misconceptions, indicating that undocumented immigrants were more advantageous to the U.S. economy, especially in states like Kentucky.…”
Section: Immigrationmentioning
confidence: 59%
“…Although inaccurate, increased blame has been placed on immigrants for higher healthcare expenditures (Mohanty et al, 2005;Stimpson, Wilson & Eschbach, 2010). Attempts to address these community concerns have been viewed as more of a political strategy rather than a public welfare concern.…”
Section: Policiesmentioning
confidence: 99%